Socio-demographic factors related to cervical cancer services utilization in urban and rural areas: Analysis of Survey Kesehatan Indonesia (SKI) data 2023 - Fitri Indrawati; Supriatin; Maretalinia (Public Health of Indonesia, 2026)
Background: Cervical cancer is a major cause of death in women in Indonesia. It can be detected through screening such as Pap smears or HPV (Human Papilloma Virus) tests, but the utilization of screening is still low, especially in rural areas, which results in many cases being at an advanced stage and affecting patient prognosis. Objective: This study aims to analyze sociodemographic factors that influence the utilization of cervical cancer screening (UCCS) in urban and rural areas in Indonesia. Methods: The 2023 Indonesian Health Survey (SKI/ Survei Kesehatan Indonesia) used a cross-sectional design across Indonesia from August to October 2023. A total of 1,191,692 people were interviewed, including 296,819 women eligible for cervical cancer screening (UCCS). The study focused on UCCS utilization, with independent variables including age, education, occupation, residence, and wealth index. Data were analyzed using univariate, bivariate (chi-square), and multivariate (binary logistic regression) methods, with separate models for all respondents, urban areas, and rural areas. Results: The finding of this study shows that 91.53% of respondents, both urban and rural, never utilized cervical cancer screening (UCCS). UCCS utilization is higher among women of reproductive age (9.23%), highly educated (15.96%), working in the formal sector (12.66%), and residing in urban areas (9.70%). The richest users (14.65%) are also higher than the poorest (5.51%). The multivariate analysis showed that women not in reproductive age were less likely to utilize cervical cancer screening, with varying probabilities depending on education, occupation, and wealth. Women with higher education, formal employment, and higher wealth were more likely to utilize screening, with the richest showing the highest likelihood. The urban model showed the best fit, with a higher pseudo-R2 (3.75%) compared to the rural model (1.68%). Conclusion: Socio-demographic factors such as age, education, occupation, and wealth significantly influence cervical cancer screening utilization in Indonesia. Higher utilization is observed among reproductive-aged women, those with higher education, formal employment, and wealthier groups, with urban areas showing better utilization rates than rural areas.  Keywords: cervical cancer screening; sociodemographic; Survey Kesehatan Indonesia (SKI); urban and rural areas